The Influence of Discipline and Work Environment on Employee Performance Through Job Satisfaction at the Telanaipura District Office - Wahyudi, Totong; Zahari, M.; Sudirman, Sudirman (Dinasti International Journal of Management Science, 2025)
This study aims to determine and describe the picture of discipline, work environment, job satisfaction and employee performance at the Telanaipura District Office and to determine and analyze the influence of discipline and work environment on employee performance through job satisfaction at the Telanaipura District Office. This type of research uses descriptive verification research. The data collection method uses a questionnaire. The sampling technique uses the census method. This study uses the PLS analysis method which consists of testing the outer model and inner model. From the PLS analysis shows that discipline and work environment have a positive and significant influence on employee job satisfaction at the Telanaipura District Office. In addition, discipline, work environment, and job satisfaction are also directly proven to have a positive and significant influence on improving employee performance. Not only direct influence, discipline and work environment also have an indirect influence on employee performance through increasing job satisfaction.